Penelitian Terapi Berbasis Sel Perkembangan Baru dalam Immunoterapi dan Gen Theraphy - Nayla Fazilla Nadin; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Research into cell-based therapies has grown rapidly in recent years, particularly in the context of immunotherapy and gene therapy. Cell-based therapy is an innovative approach that uses living cells, such as genetically modified T cells, to recognize and destroy cancer cells or other diseases. Additionally, developments in gene therapy allow scientists to edit or repair damaged genes, thereby restoring normal cell function. This research aims to explore recent developments in cell-based therapies, as well as their impact on immunotherapy and gene therapy. The main focus is on methods used to modify cells, such as CRISPR/Cas9 technology, as well as techniques to improve the ability of immune cells to target and kill cancer cells. The research also covers the challenges faced in this therapy, including the risk of side effects, genetic stability, and sustainability of transplanted cells. The research results show that cell-based therapies offer new hope in the treatment of difficult-to-treat diseases, such as cancer and rare genetic disorders. However, further research is still needed to ensure its long-term safety and effectiveness. This research is expected to provide in-depth insight into the potential and challenges of cell-based therapies, as well as providing a basis for future clinical development.